Public service ethics in local self-government - Joković, Milica (Sociološki pregled, 2021)
Within different ethical approaches, public service ethics belongs to deontological ethics. It encompasses the moral culture of employees, professional integrity, and public service integrity in institutions. Public service ethics is based on the ethical principles of professionals: autonomy, benevolence, taking care not to inflict harm on others, and fair conduct. Professional associations are the guarantors of practising and respecting the ethical principles of professionals. The acceptance of and adherence to ethical principles of professional associations is embodied through self-regulation in the codes of ethics. The codes of ethics are based on ethical principles of professionals: accountability, openness, accessibility, transparency, exemplarity, respect, and politeness.